Proposed Amendment on the Reform of the IMF Executive Board and Fourteenth General Review of Quotas : Status of Acceptances and Consents. (Policy Papers; Policy Paper ;, 2013)
A stronger presumption of publication for all program-related documents could further increase publication rates, while defining prompt publication should help reduce publication lags. Streamlining external communication products could reduce the risk of inconsistent messaging. The review also presents new evidence on evenhandedness with now only few cases not fulfilling the criteria for modifications under the policy. It nevertheless suggests measures to strengthen monitoring in this area. The review sets out the Fund's policies on confidential information, and proposes that staff systematically explains these policies in its interactions with country authorities. In response to recent surveillance reforms, the review also proposes a new publication regime for multi-country documents. Staff sees the introduction of a publication regime for a new category of multi-country documents as the best way to ensure that the Fund publishes candid multilateral surveillance, while respecting members' needs. Similarly, the modification rules for country documents will need to be adapted to take into account the implications of the Integrated Surveillance Decision (ISD).